Approximation of Fixed Points for Mean Nonexpansive Mappings in Banach Spaces. (19th June 2021) - Ahmad, Junaid; Ullah, Kifayat; Arshad, Muhammad; de la Sen, Manuel
Abstract : In this paper, we establish weak and strong convergence theorems for mean nonexpansive maps in Banach spaces under the Picard–Mann hybrid iteration process. We also construct an example of mean nonexpansive mappings and show that it exceeds the class of nonexpansive mappings. To show the numerical accuracy of our main outcome, we show that Picard–Mann hybrid iteration process of this example is more effective than all of the Picard, Mann, and Ishikawa iterative processes.